ANALISIS KESTABILAN LERENG PIT C4 DAN D2 ROTO SELATAN PT. PAMAPERSADA NUSANTARA DISTRIK KIDECO KALIMANTAN TIMUR - Herawadi, Dedi (IST AKPRIND YOGYAKARTA, 2017)
Slopes mine is an important part of a mining activity. Slopes mine, slope stability can cause problems such as landslides and disrupting mining operations. The study was conducted to obtain the slope geometry that is safe and stable. Hypotheses that the slope is stable with the value of the safety factor of 1.5 (Sostrodarsono, Suyono). Single slope stability analysis is done for each material making up the slope in the form of sandstone, mudstone, and coal at 100% Saturated as well as the overall slope value (FK) 1,5. The simulation of single slope or in whole, the simulation is done by changing the height and angle of the slope in order to obtain the value of the safety factor (FK) which is safe and stable. This study uses Hoek and Bray and methods Bishop on total water saturated conditions. Single slope stability analysis results obtained by their eighth single slopes with FK values <1.5 is on the C4 West above, C4 lower west, D2 East Upper, D2 East under, and D2 West below and 3 overall slope C4 West, East D2, D2 West. Based on the analysis, simulation single slope and slope overall is for single slope with high-level geometry of 8-11 meters with a slope angle 50o and for the overall slope, slope C4 West with a height of 60 meters and a slope angle 29o, D2 East with a high slope 70 meter and the angle of 26o, the slope D2 West with 86 meters height and the angle of 25o. Application of slope geometry simulation results can reduce the potential of landslides on the slopes of the mine with FK above the reference value of 1.5.